Hubungan Kualitas Pelayanan Terhadap Loyalitas Pasien Melalui Kinerja Pelayanan Rumah Sakit Dan Kepuasan Pasien Sebagai Variabel Mediasi - Shafa Dimas Saputra; Rahayu Puji Suci; Armanu Thoyib; Asih Tri Rachmi Nuswantari; Aji Suraji; Adya Hermawati (Journal of Innovation Research and Knowledge, 2026)
Patient loyalty is an important indicator of successful hospital services because it reflects the continuity of service utilization. This study aims to analyze the effect of service quality on outpatient patient loyalty, with hospital service performance and patient satisfaction as mediating variables at Siaga Al Munawwarah Hospital. This study employed a quantitative approach with a cross-sectional design. A total of 150 outpatients were selected using purposive sampling. Data were collected through questionnaires that had met the validity and reliability requirements and were subsequently analyzed using PLS-SEM with SmartPLS 4. The results showed that service quality contributed to improvements in hospital service performance (β = 0.821; p < 0.001), patient satisfaction (β = 0.800; p < 0.001), and patient loyalty (β = 0.228; p = 0.026). Patient satisfaction also increased patient loyalty (β = 0.450; p < 0.001), whereas hospital service performance did not demonstrate a significant direct contribution to patient loyalty (β = 0.136; p = 0.404). The mediation analysis indicated that patient satisfaction served as a partial mediator (VAF = 51.43%), while hospital service performance did not function as a mediator (VAF = 16.00%). The research model demonstrated a relatively good explanatory capability, with R² values of 0.674 for hospital service performance, 0.640 for patient satisfaction, and 0.596 for patient loyalty. Thus, improving patient loyalty can be more effectively achieved by enhancing service quality in ways that increase patient satisfaction. Therefore, hospitals should prioritize improving service quality oriented toward patients’ needs and expectations as a strategy to strengthen patient loyalty